Mechanism of Eravacycline Resistance in Clinical Enterococcus faecalis Isolates From China - Wen, Zewen; Shang, Yongpeng; Xu, Guangjian; Pu, Zhangya; Lin, Zhiwei; Bai, Bing; Chen, Zhong; Zheng, Jinxin; Deng, Qiwen; Yu, Zhijian (Frontiers in Microbiology, 2020)
Opportunistic infections caused by multidrug resistant Enterococcus faecalis strains are a significant clinical challenge. Eravacycline (Erava) is a synthetic fluorocycline structurally similar to tigecycline (Tige) that exhibits robust antimicrobial activity against Gram-positive bacteria. This study investigated the in vitro antimicrobial activity and heteroresistance risk of Eravacycline (Erava) in clinical E. faecalis isolates from China, along with the mechanism of Erava resistance. A total of 276 nonduplicate E. faecalis isolates were retrospectively collected from a tertiary care hospital in China. Heteroresistance to Erava and the influence of tetracycline (Tet) resistance genes on Erava susceptibility were examined. To clarify the molecular basis for Erava resistance, E. faecalis variants exhibiting Erava-induced resistance were selected under Erava pressure. The relative transcript levels of six candidate genes linked to Erava susceptibility were determined by quantitative reverse-transcription PCR, and their role in Erava resistance and heteroresistance was evaluated by in vitro overexpression experiments. We found that Erava minimum inhibitory concentrations (MICs) against clinical E. faecalis isolates ranged from ≤ 0.015 to 0.25 mg/l, even in strains harboring Tet resistance genes. The detection frequency of Erava heteroresistance in isolates with MICs ≤ 0.06, 0.125, and 0.25 mg/l were 0.43% (1/231), 7.5% (3/40), and 0 (0/5), respectively. No mutations were detected in the 30S ribosomal subunit gene in Erava heteroresistance-derived clones, although mutations in this subunit conferred cross resistance to Tige in Erava-induced resistant E. faecalis. Overexpressing OG1RF_RS00630 (encoding a bone morphogenetic protein family ATP-binding cassette transporter substrate-binding protein) in E. faecalis increased the frequency of Erava and Tige heteroresistance, whereas OG1RF_RS12140, OG1RF_RS06145, and OG1RF_RS06880 overexpression conferred heteroresistance to Tige only. These results indicate that Erava has potent in vitro antimicrobial activity against clinical E. faecalis isolates from China and that Erava heteroresistance can be induced by OG1RF_RS00630 overexpression.